2018
DOI: 10.1155/2018/8672407
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiochemotherapy with a 23-Month Overall Survival Time in a Patient after a Surgery due to Splenic Hemangiosarcoma Rupture: A Case Report with the Literature Review

Abstract: Spleen sarcoma is one of the most rare soft tissue malignancies. The annual incidence is 0.14–0.25/1,000,000 and the average age of diagnosis is 50 to 73 years. The incidence of this cancer has been increasing. Treatment of choice is surgical splenectomy, which rarely gives good results due to the aggressive course of the disease as well as the high potential for metastasis. Overall survival in primary spleen sarcomas as described by various authors is between 4 and 14 months. 80% of patients after spleen rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Rupture of the splenic tumor leads to early metastasis to other intraabdominal organs; hence, it is known as the worst prognostic factor [14]. Worth mentioning, in contrast to the slight male predominance reported earlier, most patients who presented with spontaneous splenic rupture due to primary angiosarcoma were females, with F/M ratio of 1.6:1 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. This surgical emergency may affect a wide age range of patients, with the youngest patient being 17 years old female [17], while the oldest was a female in her 80s, reported by Sivelli et al [25].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture of the splenic tumor leads to early metastasis to other intraabdominal organs; hence, it is known as the worst prognostic factor [14]. Worth mentioning, in contrast to the slight male predominance reported earlier, most patients who presented with spontaneous splenic rupture due to primary angiosarcoma were females, with F/M ratio of 1.6:1 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. This surgical emergency may affect a wide age range of patients, with the youngest patient being 17 years old female [17], while the oldest was a female in her 80s, reported by Sivelli et al [25].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The most common clinical presentation following spontaneous rupture of the spleen was acute upper abdominal pain reported by all patients. Hemodynamic instability was also a common presentation as well, documented in 68% of patients with spontaneous rupture [ 15 , 17 , 19 , 21 , 23 - 27 , 29 - 31 , 33 ]. In statistical terms, hemodynamic instability may develop in up to 21% of patients with angiosarcoma of the spleen.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…19 However, Bilski et al reported a case with postoperative survival of a patient of PSA with splenic rupture for 23 months with adjuvant radiochemotherapy. 20 Kohutek et al also observed prolonged survival (more than 10 years) in their patient after surgery with use of postoperative radiotherapy and bisphosphonates, doxorubicin and paclitaxel based chemotherapy at three different times. 21…”
Section: Discussionmentioning
confidence: 89%